Meniti Kegamangan Mencapai Harmoni: Kajian Antropologi terhadap Hukum yang Berkenaan Tanah pada Masyarakat Osing-Banyuwangi - Dominikus, Rato (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2005)
The aimed of this study to understand the law relating to land in cosmology of Osing society and the cosmology of Osing society.